Analisis Permasalahan Dan Solusi Pembiayaan Murabahah Pada Kspps Karisma Kantor Cabang Grabag - Dimas Daib Dzakiansyah; Chaidir Iswanaji (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Murabahah financing is the dominant product in Islamic microfinance institutions due to its simple mechanism and fixed margin certainty. However, this type of financing still carries the potential risk of non-performing financing (NPF). This study aims to analyze the condition of murabahah financing and to identify the contributing factors and mitigation strategies for non-performing financing at KSPPS Karisma Grabag Branch Office. This research employs a qualitative approach using a case study method through interviews, observations, and documentation. The findings indicate that the level of non-performing financing ranges from 1% to 3%, which is still considered under control. The main contributing factors include unstable income, multiple financing obligations in other institutions (over-credit), as well as health and employment issues of members. The mitigation strategies implemented consist of persuasive approaches, direct visits, issuance of warning letters, and financing rescheduling and restructuring. These strategies are considered effective in maintaining financing quality stability. The study recommends strengthening feasibility analysis, classifying members based on financing categories, and improving monitoring systems to minimize the risk of non-performing financing.